2020
DOI: 10.1016/j.jue.2020.103257
|View full text |Cite
|
Sign up to set email alerts
|

The effect of natural disasters on economic activity in US counties: A century of data

Abstract: More than 100 natural disasters strike the United States every year, causing extensive fatalities and damages. We construct the universe of US federally designated natural disasters from 1920 to 2010. We find that severe disasters increase out-migration rates at the county level by 1.5 percentage points and lower housing prices/rents by 2.5-5.0 percent. The migration response to milder disasters is smaller but has been increasing over time. The economic response to disasters is most consistent with falling loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(124 citation statements)
references
References 62 publications
(63 reference statements)
9
102
0
1
Order By: Relevance
“…Figure 3a shows estimated effects of Hurricane Katrina on annual mortality (equation 2, solid black lines) as well as on cumulative mortality (equation 3 Using a value of $100,000 per life-year (Cutler, 2004) and a discount rate of 3 percent (Siegel, 1992) (Strobl, 2011;Deryugina, 2017;Boustan et al, 2017).…”
Section: Annual Mortality and Relocationmentioning
confidence: 99%
“…Figure 3a shows estimated effects of Hurricane Katrina on annual mortality (equation 2, solid black lines) as well as on cumulative mortality (equation 3 Using a value of $100,000 per life-year (Cutler, 2004) and a discount rate of 3 percent (Siegel, 1992) (Strobl, 2011;Deryugina, 2017;Boustan et al, 2017).…”
Section: Annual Mortality and Relocationmentioning
confidence: 99%
“…In terms of total population, some studies have found that the typical disaster leads to net population gain or an acceleration in total growth (Pais and Elliott 2008;Schultz and Elliott 2013). Other studies have documented a net out-migration (Boustan et al 2017), a reduction in population growth (Logan et al 2016), or even no change at all (Deryugina 2017). Many studies also have highlighted considerable effect heterogeneity (Elliott and Pais 2010;Fussell et al 2017;Logan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the effects on total population, sociologists and demographers also model changes among various demographic subgroups. Although some have found a net out-migration of disadvantaged groups, such as racial minorities and impoverished individuals (Boustan et al 2017;Elliott 2015), other studies have suggested that wealthy and White people move away and that lower-income and racial minorities are stuck in place (Logan et al 2016). These disparate findings signal a need for further research with rigorous empirical strategies and refined theoretical models.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut IMF, bencana alam juga memberikan dampak negatif dan signifikan terhadap pertumbuhan ekonomi serta dapat menyebabkan terjadinya pemburukan keseimbangan perdagangan maupun fiscal (Lee et al, 2018). Selain itu, daerah yang mengalami bencana parah akan memiliki migrasi penduduk keluar yang besar, harga rumah di daerah terdampak turun drastis, serta meningkatnya tingkat kemiskinan pada daerah terdampak bencana (Boustan et al, 2017).…”
Section: Pendahuluanunclassified